PEMENFAATAN BUAH PEPAYA TERHADAP PENINGKATAN KADAR HEMOGLOBIN PADA REMAJA SISWI SMP PERGURUAN ISLAM MODERN AMANAH MEDAN TAHUN 2023 - Ivansri Marsaulina (Jurnal Maternitas Kebidanan, 2023)
According to the World Health Organization, the incidence of anemia in adolescent girls in developing countries is around 53.7% of all adolescent girls. Teenage girls are more susceptible to anemia, the monthly menstrual cycle is one of the causes. Efforts to overcome anemia by administering blood supplement tablets by accelerating the absorption of Fe with vit. C from papaya fruit. The aim of this study was to determine the effectiveness of Fe absorption with papaya on increasing Hb. Types of quantitative research, experimental research methods and quasi-experimental designs. The research was conducted at Amanah Modern Islamic College Middle School, Medan City. The population in this study was 50 young women who experienced anemia. The sample in this study used a total population of 50 young women who experienced anemia at the Amanah Islam Islamic College Middle School, Meda City. This research was carried out by checking hemoglobin and providing treatment in the form of giving papaya and Fe to the intervention group and giving Fe to the control group for one month. The data analysis used was univariate and bivariate analysis with the t test. The results of data processing and analysis showed that the increase in Hb in the group given Fe intervention with papaya was greater than in the group given Fe alone (p = 0.034). Effective Fe absorption with papaya on increasing Hb.The conclusion of the research shows that there is effectiveness of Fe absorption with papaya on increasing Hb. at Amanah Islamic College Middle School, Medan City. It is hoped that young women should consume Fe tablets properly and consume fruits that are high in vitamin C, thus making it easier for the application of iron in the body to increase hemoglobin levels in the blood.